Freedom of speech and information hygiene are the most basic criteria of democracy (Herald of Journalism, 2021)
The place and activity of freedom of speech in the formation of public relations, factors affecting it, legal issues of freedom of speech are topical issues of journalism. In journalism, the phenomena of influence on social development through the ways of presenting information are also important. The protection and realization of human rights, ensuring through the mass media are related to the openness of information. Its core is the freedom of the fourth power, freedom of speech.The purpose of the article is to consider a scientifically based definition of freedom of speech, to determine the need for freedom of speech in the development of society, activities in ensuring constitutional and other human rights, to show the factors affecting the implementation of freedom of information, to analyze the ways of transmitting information, to prove the activity of information hygiene, the correct use of information as a criterion of a democratic society.The scientific and practical value of the research work consists in the fact that a scientific conclusion is made about the concepts of freedom of speech, freedom of information, ways of transmitting information, information hygiene, and their activity in changing social relations is proved. The article gives an idea that the communication language is used when transmitting information and all its functional activities are used.It is proved that the main result of a scientific article is the meaning of freedom of speech, the most important means of journalism is the provision of information. The types and methods of information transmission are analyzed. Thus, the correctness of the open transmission of information, compliance with information hygiene when transmitting information was demonstrated. In the conclusion of the research work, it is concluded that freedom of speech is the key to the impartial transmission of information.Key words: freedom of speech, information flow, information transfer, information hygiene, psycholinguistic expression, media space, journalism instrument.